A new variety of Wurfbainia villosa (Zingiberaceae) from India - Thomas, V.p.; Dan, M.; Saleem, M.; Binoy, T.t.; Sabu, M. (Phytotaxa, 2026)
A new variety of Wurfbainia villosa from Arunachal Pradesh is described. Detailed descriptions, photographs, details of distribution etc. are provided.